Practical statistics - Cohen, S.S (Edward Arnold, a division of Hodder & Stoughton, 1988)
An outline of the concept and practical uses of statistics, aimed at less mathematical readers. It covers a range of the practical statistical techniques which are now indispensable in so many areas of science and business and it makes extensive use of worked examples from many disciplines